(untitled) (Review Journal of Neurological & Medical Sciences Review, 2025)
Bacteria impact the soil, animals, food consumers, and ecology as a whole and have developed a significant tolerance to overuse of antibiotics. In addition to resistance, they caused several toxicity issues. Around the world, chemical compounds are harming crops and agricultural commodities. In order to address these growing problems, it is becoming more and more necessary to find and create agricultural and/or botanical alternatives. Using an antibacterial agent derived from plant extract, which is a natural source of secondary metabolites and works well against bacteria that cause disease, is an alternate option. The most promising plant in terms of antibacterial properties is Viburnum grandiflorum. The aim of the proposed study is to investigate the antibacterial activity of the methanolic crude extract of Viburnum grandiflorum leaves and epicarp against the pathogenic effects of P. aeruginosa and P. syringae, which cause many illnesses in humans, animals, and plants. The maceration step produced the crude methanolic extract. The zone of inhibition against P. syringae and P. aeruginosa was evaluated by means of the agar well diffusion technique used to evaluate the antibacterial profile. The findings demonstrated that the plant’s leaf and epicarp crude extract had the potential to be employed as an antibacterial agent due to its ability to inhibit bacterial growth and the presence of a zone of inhibition. In the future, various dilutions of various plant sections can be tested on various bacterial strains to further assess the plant’s potential. Key words: Viburnum grandiflorum, Crude extract, Antibacterial Agent